Análise da livre concorrência e competitividade no setor elétrico brasileiro - NASCIMENTO, José Carlos Alves do (2007)
In this work the relevant aspects of free competition and competitivity in the Brazilian electric sector after deregulation initiated in 1995 are analyzed. The earlier model of the electric sector, a State monopoly, moved for a desverticalized structure with the separation of the sectors of generation, transmission and distribution. With this scenario as background it was performed a retrospect of the more important aspects of the restructuring process, being identified the regulatory outline created for the conception of a free market model that culminated with the changes occurred from promulgation of legislation, in 2004, which defined a new regulatory environment for the Brazilian electric sector. In this specific case are distinguished the performance of the main institutions of the sector, the free access to the electric networks, the economic signal represented by the tariffs, the free and captive consumers, as well as the commercialization process. The risks and challenges, generated by the introduction of the free market model, were analyzed, verifying if the implemented rules facilitate or difficult the free competition and competitivity. It is concluded that in Brazil the free competition and competitivity of the electricity market agents are in a developing process and enhancements and reforms to the wholesale electricity market rules are required. The difficulty for the regulator is to meet the yearnings of the commercializators that wait attitudes that make possible the increase of the portfolio of the potentially free consumers against the ones of distribution concessionaires that may have reduction in their profits due the increase of migration from captive to free consumers. On the other hand, the coexistence of characteristics of the monopolist and free market models has been proved where the tendencies of that hybrid model are not clearly defined.